2005
DOI: 10.1111/j.1365-2214.2005.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the factors influencing the paediatrician–parents relationship: the importance of the socio‐demographic characteristics of the mothers

Abstract: Our experience suggests that maternal anxiety and physicians' interpretation of parental expectations are important factors to take into account during the visit. The paediatricians are not always good predictors of parental expectations. Younger mothers, with a lower level of education and with less experience need more time, more information and support by paediatricians. They are more likely to request therapy, are less satisfied, more easily influenced and likely to follow mass-media advice, rather than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We found that one-third of respondents complained that physicians seldom or even never explained their children’s illness during healthcare visits. Several studies of the patient-physician encounter have reported limited interactions between physicians and patients, mainly owing to the lack of time to talk facing the long line of outpatients waiting or to the lack of a regulated procedure for assisting patients in understanding the disease and treatment [23,30]. Our findings demonstrate the important role of physicians in the appropriate use of antibiotics in rural China, illuminating the urgent need for communication training and professional education among physicians.…”
Section: Discussionmentioning
confidence: 76%
“…We found that one-third of respondents complained that physicians seldom or even never explained their children’s illness during healthcare visits. Several studies of the patient-physician encounter have reported limited interactions between physicians and patients, mainly owing to the lack of time to talk facing the long line of outpatients waiting or to the lack of a regulated procedure for assisting patients in understanding the disease and treatment [23,30]. Our findings demonstrate the important role of physicians in the appropriate use of antibiotics in rural China, illuminating the urgent need for communication training and professional education among physicians.…”
Section: Discussionmentioning
confidence: 76%
“…In the course of our review, we located 19 studies [7,53–70] that exclusively used qualitative methodology. Only two of the studies included [33,48], however, referred to the use of qualitative methodology as a preliminary stage for identifying factors related with the prescription of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that 60% of children treated with an antibiotic by the RGP received at least one amoxicillin prescription indicates that the acceptance of therapy with this drug can be achieved in most families. Parental expectation is often an important factor influencing antibiotic prescribing, and it has been demonstrated that younger mothers with a lower level of education and less experience need more time, information and support by paediatricians . Educational interventions focused on parents have been successful in reducing inappropriate requests for prescriptions …”
Section: Discussionmentioning
confidence: 99%